Parenting Support : Key Transformational Instrument of Child and Human Development Policies - Trends in EU Countries and Discussion on Parenting Policies in Bulgaria - World Bank (World Bank, Washington, DC, 2019)
This policy note is developed with the aim to inform the planning and implementation of the policy goals toward parenting support in Bulgaria. First, it summarizes the trends and concepts in parenting policies that influence the evolution of programs across Europe and other countries. Second, it offers a brief review of parenting components under the public policies in Bulgaria to foster discussions on the policy arrangements and implementation programs design needed to strengthen the outcomes of the existing systems and human development policies. Possible entry points across sector services, that can be easily employed to initiate positive and flexible programs are discussed. Finally, possible steps for parenting support development are proposed together with 19 examples for parenting policies from European counties. The examples include national strategies and programs approaches, parenting support delivery and an information campaign, collected in the Annex as a reference and program development support tool.